2020
DOI: 10.1590/1806-9061-2020-1274
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Bacillus Subtilis and Pediococcus Acidilactici Mix on Serum Biochemistry, Growth Promotation of Body and Visceral Organs in Lohmann Brown Chicks

Abstract: Recently the use of antibiotic growth promoter (AGPs) in poultry feed is banned in China, leading to the increasing demand for AGPs substitutes. Probiotics have been considered as a potential substitute. The purpose of this study was to evaluate the effects of probiotic on serum biochemistry, and growth promotion of body weight and visceral organs and in Lohmann Brown chicks aged 0 to 9 weeks. Five hundred and forty 1-day-old male chicks were randomly divided into three groups, with six replicates and 30 chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Experimental reports have supported that there are no significant adverse effects caused by probiotic strains of B. subtilis in acute toxicity tests [19,20] or in organs [21], such as the heart and liver, indicating that B. subtilis is safe and non-toxic to mammals [22]. It has also been reported that specific oral serum IgG and intestinal mucosal SIgA, in mice, can be induced by the administration of recombinant B. subtilis spores [23].…”
Section: Introductionmentioning
confidence: 95%
“…Experimental reports have supported that there are no significant adverse effects caused by probiotic strains of B. subtilis in acute toxicity tests [19,20] or in organs [21], such as the heart and liver, indicating that B. subtilis is safe and non-toxic to mammals [22]. It has also been reported that specific oral serum IgG and intestinal mucosal SIgA, in mice, can be induced by the administration of recombinant B. subtilis spores [23].…”
Section: Introductionmentioning
confidence: 95%
“…Probiotics are new feed additive that could be used instead of antibiotics. Probiotics exert beneficial effects on the body via a range of complicated and interconnected pathways (Yu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are new feed additive that could be used instead of antibiotics. Probiotics exert beneficial effects on the body via a range of complicated and interconnected pathways (Yu et al, 2020). Production efficiency comprising BWG, FI and FCR are the major parameters used to analyse the economic benefits of poultry production (S. Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…O gênero Bacillus também achado em grande abundancia, parece ter origem nos dejetos das aves, uma vez que a administração de probióticos com B. subtillis é amplamente recomendado pelos pesquisadores, substituindo antibióticos e promovendo maior desempenho de crescimento corpóreo e visceral (Ciurescu et al, 2019;Yu et al, 2020).…”
Section: Que Relataramunclassified